Linux for beginners - Pezet, Don; Rodrick, Mike; Memos, Zachary (Packt Publishing Ltd., 2024)
The course begins with an introduction to Linux, offering insights into its importance and widespread use in today's tech-driven world. You'll learn why Linux is the backbone of many servers, devices, and systems, and how its open-source nature fosters innovation and customization. The course focuses on choosing a Linux distribution, guiding you through the myriad of options available and helping you select the one that best fits your needs. This segment is crucial for understanding the diversity within the Linux ecosystem and how it caters to different user preferences and requirements. Next, we delve into choosing a desktop environment, emphasizing the significance of the user interface in your day-to-day interaction with Linux. You'll explore popular desktop environments, their features, and how to select one that aligns with your usability and aesthetic preferences. The course wraps up with a detailed walkthrough on installing software on Linux, covering various package managers and installation methods. This section is designed to equip you with the skills to extend the functionality of your Linux system and customize it to your liking.
Online resource; title from title details screen (O'Reilly, viewed March 19, 2024)
Keywords: Linux; Operating systems (Computers); Computer science; Systèmes d'exploitation (Ordinateurs); Informatique; operating systems; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet